Clinical Features, Laboratory Findings and Complications of Scrub Typhus in South Indian Children - Gopalakrisna, Manjunath Vaddambal; Suryaprakash, Hedda; Kumar, G. Shankarappa Vijay; Kumar, Kalenahalli Jagadish; Murthy, Doreswamy Srinivasa (Journal of Nepal Paediatric Society, 2017)
Introduction: Scrub typhus clinical features are non-specific and resemble other tropical infections like malaria, dengue and typhoid fever. Therefore appropriate gold standard laboratory tests are necessary to confirm the diagnosis of scrub typhus. Aim of this study was to determine the incidence, clinical features, laboratory data and complications of scrub typhus in South Indian Children. Materials and Methods: Children with fever of more than seven days who were tested negative for common tropical infections were subjected to IgM-IFA for scrub typhus. Results: Out of 857 children, 74 were eligible for IFA test. Out of these, 27(3.1%) tested positive for scrub typhus. Clinical features included hepatomegaly (96.3%), generalized lymphadenopathy (81.5%), splenomegaly (81.5%), hypotension (59.3%), rash (14.8%), eschar (7.4%), thrombocytopenia (66.7%), elevation of SGOT (85.2%) and SGPT (81.5%). Complications include hepatitis (14.8%), pneumonia (14.8%), myocarditis (14.8%) meningoencephalitis (3.7%) and MODS (3.7%). Conclusion: Scrub typhus should be considered in the differential diagnosis of a febrile child having hepatosplenomegaly, lymphadenopathy, liver dysfunction and thrombocytopenia.